Stated choice methods analysis and applications - Louviere, Jordan J.; Hensher, David A. 1947-; Swait, Joffre (Cambridge University Press, 2000)
Understanding and predicting the behaviour of decision makers when choosing among discrete goods has been one of the most fruitful areas of applied research over the last thirty years. An understanding of individual consumer behaviour can lead to significant changes in product or service design, pricing strategy, distribution channel and communication strategy selection, as well as public welfare analysis. This graduate and practitioner guide, first published in 2000, deals with the study and prediction of consumer choice behaviour, concentrating on stated preference (SP) methods - placing decision makers in controlled experiments that yield hypothetical choices - rather than revealed preferences (RP) - actual choices in the market. It shows how SP methods can be implemented, from experimental design to econometric modelling, and suggests how to combine RP and SP data to get the best from each type. The book also presents an update of econometric approaches to choice modelling
Erscheinungsdatum laut E-Book-Frontpage: July 2010
Keywords: BUSINESS & ECONOMICS / Consumer Behavior; Consumer behavior / Mathematical models; Decision making / Mathematical models; Besliskunde; Consumentengedrag; Wiskundige modellen; Consommateurs / Comportement / Modèles mathématiques; Prise de décision / Modèles mathématiques; CONSUMIDOR.; COMPORTAMENTO DO CONSUMIDOR.; MODELOS MATEMÁTICOS.; Mathematisches Modell; Wirtschaft; Kaufentscheidung; Präferenzfunktion; Verbraucherverhalten